Tendências de sucesso no percurso acadêmico do alunado na UFRN - Granja, Veruska de Araújo Vasconcelos (2012)
Enter the University and remain in it is a challenge for all students who leave high school and enter this level. The aspiration for a graduation occur by several factors, which have decisive impact on the personal lives of individuals who acquire training in higher education, both as regards the professional capacities as economic opportunity. There are several possible trajectories to get into a college. Students can be classified by their success or failure in performance due to multiple intervening factors that interact among themselves. The purpose of this work is to identify and characterize the factors that reveal trends of success and failure in academic performance of UFRN students. From this general goal, broke out the following specific objectives: to analyze the problems of expanding access to and restructuring of higher education in Brazil and UFRN; explicit definitions of success and failure in higher education; identify national trends and international help to determine the success and failure of students in UFRN. Therefore, we conducted an extensive literature review on the subject and analyzed secondary data from official national, regional and local statistical sources on the subject. In the delimitation of the data, the research population refers to students who entered the UFRN through the vestibular, in the years 2000 to 2010, and who attended at least one (1) semester. In the light of the analysis, the theoretical framework interpretation and the investigative data, it was possible to identify the major factors that affect the categories of success and failure in this university, which highlight the following: the policies adopted by UFRN have provided access mechanisms and student assistance policies, trying to supply the needs of students for them to have a good academic performance, or success in their courses; in addition, the chosen focus of analysis showed that, within the same area, there is not significant difference in the performance of students coming from less favored social and educational contexts, which does not occur when analyzing the success rates between students from different areas of knowledge. The trajectory of interpretative analysis of the results presented in this paper enables to raise points of discussion in various forums and higher councils in order to increase the academic indices of its students. It also enables to promote strategies of guidance and student support for that he persists in his choice